ANALYSIS OF M. DIEMAS ANGGARA'S (@infoasikdimas) PERSONAL BRANDING ON INSTAGRAM IN RELATION TO CULINARY TOURISM PROMOTION IN MEDAN CITY - Zalukhu, Ardimas Zain; Achiriah, Achiriah (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the personal branding strategies employed by M. Dimas Anggara through the Instagram account @infoasikdimas in promoting culinary tourism in Medan City. Amid the growing role of social media as a digital promotional platform, personal branding has become a crucial element in shaping the image and influence of an influencer. This research adopts a descriptive qualitative approach, utilizing data collection techniques such as content observation, digital documentation, and the distribution of questionnaires to the followers of the @infoasikdimas account. The human brand theory developed by Susan Fournier and Thomson serves as the main framework for understanding the dimensions of authenticity, emotional closeness, and personal appeal in the individual brand formation process. The findings indicate that the @infoasikdimas account exhibits strong elements of personal branding, such as consistency in showcasing local culinary content, authenticity in delivery, and active engagement with the audience. The presented content is not only visually appealing but also informative and communicative. This strategy successfully builds trust and loyalty among followers and has a direct impact on increasing exposure and consumer interest in the recommended culinary spots. Furthermore, Dimas's role as a micro-influencer contributes to the promotion of culinary MSMEs and supports the narrative of Medan City as a friendly and authentic culinary tourism destination. Thus, this study demonstrates that strategically and authentically developed personal branding through social media can significantly contribute to the promotion of the local creative economy, particularly in the culinary tourism sector. These findings are expected to serve as a reference for creative industry players and academics in developing more effective digital branding approaches.